Education as a Pathway to Help Job Searching Military Veterans’ Transition to Civilian Life (Journal of Education and Development, 2021)
The transition from military to civilian life can be a difficult process. Two distinct samples of working United States military veterans were studied: combat (n = 56) and non-combat (n=43). The goal of this study was to investigate the specific role of furthering one’s education as a pathway to help job-searching military veterans in their transition to civilian life. Across both samples, veterans who were actively job searching had higher burnout and general exhaustion than veterans not actively searching. There was partial support for finding veterans who were actively job searching to be currently furthering their education, and for those currently furthering their education to perceive higher occupational alternatives. High percentages in both samples were currently going to school to further their education. The importance of education as a pathway to support military veterans making a successful transition to civilian life is discussed.